The Effectiveness of Flash Card Media-Oriented Group Investigation Learning Models on Learning Outcomes of Elementary Students - Aiman, Ummu; Meilani, Dian; Uslan (Postgraduate, University of Mataram, 2023)
The purpose of this study was to determine the effectiveness of the flash card media-oriented group investigation (GI) learning model on the learning outcomes of elementary students. The approach used in this study is a quantitative approach with pre-experimental methods and the type of One Group Pretest-Posttest design. With the overall population of SD Inpres Oeba 2 class V students 22 people. Sampling using nonprobability sampling saturated sampling where all members of the population are sampled. The data collection technique was obtained from a multiple choice written test. The data analysis technique used descriptive analysis and inferential statistics with the help of the SPSS version 22 application. The results showed that independent t-test data processing obtained a sig value of 0.000 <0.05, then Ha was accepted and H0 was rejected or in other words there was a significant difference between pretest and posttest classes in improving student learning outcomes in the material for the digestive tract of food in humans. Thus, the Flash Card Oriented Group Investigation (GI) learning model can improve the Learning Outcomes of Class V Students of SD Inpres Oeba 2 Kupang City.